Exploring Social Critique in the Literary Work of Film: Ali & Ratu Queens through Bourdieu's Sociological Theory - Aini, Adhisa Nur; Amilia, Fitri; Dzarna, Dzarna; Susetyo, Agus Milu (Journal of Language and Literature Studies, 2024)
Film criticism involves evaluating the quality of a work from artistic, cultural, and technical perspectives. It does not only focus on the narrative or story of the film but also includes other elements such as cinematography, acting, character development, and the conveyed themes. Therefore, this study aims to explore social critique in the film Ali & Ratu Queens using Pierre Bourdieu’s sociological approach, specifically the concepts of habitus, capital, and field as presented in the film. The research employs a descriptive qualitative method, with data drawn from the dialogues and actions of characters within the film. Data collection techniques include watching, marking, observing, and note-taking. The collected data is qualitatively analyzed by observing dialogues, identifying those that reflect Bourdieu’s theories, documenting them, classifying dialogues into categories of habitus, capital, and field, and drawing conclusions based on the analysis of these dialogues. The findings show that the film depicts habitus as a result of internalized social experiences, where economic, social, and cultural capital influences character interactions, and social and educational fields serve as arenas in which individuals compete for higher social positions. Through the application of Bourdieu’s theory, this research reveals that film can serve as an effective tool for critiquing and reflecting on the social and cultural conditions of society.